Oxyuriasis at the Department of Pediatrics, Dr. Pirngadi Hospital, Medan - Berlian Hasibuan; Mahruzzaman Naim; Azwan H. Lubis; Syahril Pasaribu; Chairuddin P. Lubis (Indonesian Pediatric Society, 1989)
During the period of 3 months (February - April 1987), a prospective study on oxyuariasis among children had been conducted at Child Health Deparment of Dr. Pirngadi Hospital Medan. All children over 8 months of age were included in this study.The diagnosis was based on the modified Scoth 's technique. Oxyuriasis ova were found in 21 out 119 children (17,65%). The peak incidence was found in the school age.